High flow nasal oxygen during procedural sedation for cardiac implantable electronic device procedures: A randomised controlled trial. Issue 8 (August 2021) - Conway, Aaron; Collins, Peter; Chang, Kristina; Kamboj, Navpreet; Filici, Ana Lopez; Lam, Phoebe; Parotto, Matteo
Abstract : BACKGROUND: High flow nasal oxygen may better support the vulnerable respiratory state of patients during procedural sedation. OBJECTIVE: The objective of this study was to investigate the effects of high flow nasal oxygen in comparison to facemask oxygen on ventilation during cardiac implantable electronic device procedures performed with procedural sedation. DESIGN: A randomised controlled trial. SETTING: The study was conducted at one academic hospital in Canada. PARTICIPANTS: Adults undergoing elective cardiac implantable electronic device procedures with sedation administered by an anaesthesia assistant, supervised by an anaesthesiologist from August 2019 to March 2020. INTERVENTIONS: Participants were randomised 1 : 1 to facemask (≥ 8 l · min −1 ) or high flow nasal oxygen (50 l · min −1 and a 50 : 50 oxygen to air ratio). MAIN OUTCOME MEASURES: The primary outcome was peak transcutaneous carbon dioxide. Outcomes were analysed using Bayesian statistics. RESULTS: The 129 participants who were randomised and received sedation were included. The difference in peak transcutaneous carbon dioxide was 0.0 kPa (95% CI -0.17 to 0.18). Minor adverse sedation events were 6.4 times more likely to occur in the high flow nasal oxygen group. This estimate is imprecise (95% CI 1.34 to 42.99). The odds ratio for oxygen desaturation for the high flow nasal oxygen group compared with the facemask group was 1.2 (95% CI 0.37 to 3.75). The difference in satisfaction with sedation scores between groups was 0.0 (95% CI -0.33 to 0.23). CONCLUSIONS: Ventilation, as measured by TcCO2, is highly unlikely to differ by a clinically important amount between high flow nasal oxygen at 50 l min −1 or facemask oxygen at 8 l min −1 . Further research with a larger sample size would be required to determine the optimal oxygen:air ratio when using high flow nasal oxygen during cardiac implantable electronic device procedures performed with sedation. TRIAL REGISTRATION NUMBER: NCT03858257